The Influence of Safety Climate and Organizational Learning on Employees’ Safety Risk Behaviour at the Jubilee Oil Fields - Bayire, F. A. (University of Ghana, 2016)
This study was conducted to investigate the impact of safety climate and organizational learning on employees’ safety risk behaviour in the oil and gas industry in Ghana. A total sample of 140 employees was conveniently selected to serve as respondents for the study. The quantitative cross-sectional research design was employed. Standardized measures were employed to assess employees’ perception of safety climate, organizational learning, and their risk behaviours. The independent samples t test, the Pearson r test, and the linear regression test were used to analyze the data. The findings showed that safety climate and organizational learning significantly reduced employees’ risk behaviour. Dimensions of safety climate namely safety communication, co-worker value for safety, and supervisor monitoring and recognition negatively predicted employees’ risk behavior but production pressure positively predicted employees’ risk behavior. Finally, gender, age, and field experience significantly influenced employees’ risk behaviour. Females, older employees, and experienced employees engaged in less risk behaviour compared to males, younger employees, and inexperienced employees. These findings have been discussed with references to relevant psychological literature and theories.
Thesis (MPhil.) - University of Ghana, 2016